The effect of yoga exercises on back pain in third trimester pregnant women at the Bunda Tessa Pratama Clinic - Lubis, Rhina Chairani; Br Saragih, Pebrina Wanti (Institute Of Computer Science (IOCS), 2024)
One of the physical changes experienced by TM III pregnant women is the increasingly lordotic shape of the back which results in TM III pregnant women experiencing back pain and if not handled properly it can affect the condition of the mother and fetus, causing complications. Yoga exercise is one option to reduce back pain in pregnant women. The aim of this study was to determine the effect of yoga exercises on back pain in pregnant women in the third trimester at the Bunda Tessa Clinic. This type of research is a quasi experiment because it measures changes in the level of maternal complaints in the third trimester after carrying out a certain action, namely antenatal yoga. This research was conducted by examining maternal complaints before (pretest) and after (posttest) antenatal yoga. Based on the results of research and discussion of research on the assessment of back pain before and after doing yoga exercises for pregnant women in the third trimester at the Pratama Bunda Tessa Clinic, with the results of statistical test calculations obtained a p value of 0.000 < 0.05, it can also be concluded that there is an effect of yoga exercises on pain. back of pregnant women in the third trimester at the Bunda Tessa Clinic.